(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Central bank independence is one of the most important factors that contribute to achieving monetary and financial stability. When a central bank is independent, it is able to make monetary decisions without interference from the government or any other entities. This study aims to measuring the extent of the Independence of the Central Bank of Syria in responding to changes in GDP and inflation Using the Taylor Curve Function. The study used historical data from the period 2002 to 2021. The statistical work methodology included descriptive analysis and graphs of the function variables, followed by testing their stability and explaining the variance inflation factor, up to estimating the function using the ARDL methodology and verifying the quality of the model. The study concluded that the coefficients of inflation and economic growth are not significant in the Taylor equation to test the independence of the Central Bank of Syria, i.e., not enjoying independence overall. The value of the interest rate sensitivity coefficient to GDP (-0.1783) is less than the expected value (1). The value of the interest rate sensitivity coefficient to inflation (-0.0063) is also smaller than the expected value (0). These results indicate that the Central Bank of Syria does not enjoy sufficient independence to act in accordance with its monetary objectives without being affected by political or economic pressures. The study recommends that it is necessary to strengthen the independence of the Central Bank of Syria by stabilizing the political and economic conditions in Syria, preventing government interference in the work of the bank, following a more flexible and transparent monetary policy, and conducting an analysis of the impact of all factors that affect on the independence of the Central Bank of Syria.